Pre-Roman copper industry had no polluting impact on the global environment - Omri Yagel; Aaron Greener; Willie Ondricek; Erez Ben-Yosef (Scientific Reports)
Abstract Among the unresolved questions about pre-Roman metallurgical industries are the extent and severity of the pollution they produced and the potential harm inflicted on the societies associated with them. Research on this topic has resulted in conflicting conclusions. Based on measurements of heavy metal enrichment in soils, archaeological sediments, plants and skeletal remains, interpretations have varied between catastrophic, global (intercontinental) effects to a restricted impact relevant only to those directly working at the furnaces. In the current study we focus on Timna Valley in the Southern Arabah (southern Israel). Based on high-resolution pXRF geochemical surveys of two smelting camps from different periods, accompanied by test excavations, we demonstrate that (1) mapping elemental concentrations in soil is an effective tool for identifying and characterizing various activity areas in archaeological sites, such as metal production, livestock penning and domestic and industrial waste disposal; (2) in Timna, the intra-site organization of production and scale of metallurgical activities changed substantially between the Early Bronze Age and the Iron Age; (3) the heavy metal enrichment (Cu/Pb) of soil due to smelting is spatially discrete, concentrated only in areas directly associated with these activities; and (4) this enrichment aligns with the spatial distribution of metallurgical waste, suggesting that lead emission to the atmosphere was minimal and that the documented heavy metals are not bioavailable. Our results, combined with a comprehensive survey of previously published data, support the minimalist interpretation of the polluting effects of metallurgical activities on ancient societies, at least for pre-Roman copper production industries.